175 Effect of age at calving on greenhouse gas emissions from simulated beef farms grazing four stockpiled forage species in late fall/early winter. (30th November 2020) - Donnelly, Megan E; Ominski, Kim; McGeough, E J; Wittenberg, Karin; Legesse, Getahun
Abstract: The impact of age at first calving (2 versus 3 yrs) and type of forage species grazed in late fall/early winter on lifetime greenhouse gas (GHG) emissions from a cow-calf herd over an 8 or 9 yr period was examined. Farm simulations, based in Manitoba, Canada, were assessed using the Holos model to determine whole-farm GHG emissions for each scenario. The baseline herd consisted of 170 cows, 6 bulls, and their progeny which were sold at weaning, apart from herd replacements. Each simulation began with 207 newborn, female calves, with GHG emissions measured annually. From October to December, 1 of 4 stockpiled forages/forage mixtures were grazed: i) standing corn (COR), ii) tall fescue/meadow bromegrass (TFM), iii) orchardgrass/alfalfa (OGA), and iv) tall fescue/alfalfa/cicer milkvetch (TAC). All other feeding phase diets did not differ across all scenarios. Herd GHG emissions (Mg CO2 e) were lower with heifers calving at 2 yrs (3, 938 ± 71 Mg CO2 e) versus 3 yrs (4, 634 ± 72 Mg CO2 e). Enteric methane (CH4 ) was the largest source of GHG emissions accounting for 66% of the total in both the 2- and 3-yr scenarios. Average enteric CH4 values were 3, 820±61, 4, 251 ± 68, 4, 887±79, and 4, 220 ± 68 Mg CO2 e for simulations grazing COR, TFM, OGA, and TAC, respectively and were inversely related to total digestible nutrient (TDN) content of the forage mixtures with 72, 54, 45 and 55% TDN. Emissions were highest from OGA, the lowest quality forage, in both calving scenarios. Nitrous oxide emissions from livestock manure were the second highest contributing source, representing 15% of total emissions. Reducing age at first calving (2 versus 3 yrs) and providing higher energy forage in late fall/early winter reduced cow-calf GHG emissions. The adoption of management strategies such as reducing age at first calving and improving forage quality for extended grazing may reduce emissions from the cow-calf sector.